A study of degradable orthopedic implant: An insight in magnesium metal matrix composites. Issue 9 (September 2022) - Adetunla, Adedotun; Fide-Akwuobi, Anthony; Benjamin, Henry; Adeyinka, Adebayo; Kolawole, Adenike
Abstract: Majority of the properties required for orthopedic implants operation are demonstrated by magnesium and its alloys, however the metal degrades rapidly in the body's environment. Therefore, a magnesium-based metal matrix composite capable of safely and gradually degrading in the body within the required healing time is required, thereby eliminating the need for a secondary surgery. In this study, three AZ31 Mg alloy samples with 50% reinforcement of Calcium Carbonate Powder, 25% reinforcement of CaCo3, and no reinforcement (As-received) were developed via stir-casting technique. X-ray Fluorescence was used to determine the chemical composition of the alloy while the microstructural characterization was determined by SEM. Furthermore, tensile, impact, corrosion and hardness tests were performed to determine the mechanical properties of the composites. The findings show that the newly fabricated alloy (AZ31B Mg/CaCO3 ) has a good chance of being employed in orthopedic applications where corrosion resistance is critical, as it shows an improved tensile and hardness properties when compared with the unreinforced Az31 Mg alloy. Abstract : Magnesium alloy; Mechanical properties; Orthopedic implants; Reinforcement.